Modelagem generalizada do problema de planejamento da expansão de sistemas de transmissão - Nascimento, Edgar [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this work and in order to solve the long-term transmission expansion planning problems, a novel mathematical model which is based on a change in the concept of expanding a transmission system is presented. In traditional transmission system expansion planning, only the additions of candidate lines are considered. In this work, a new concept of transmission system expansion planning is to find a new solution for the base topology where all the lines are temporarily disconnected and the implementation of these lines are reconsidered when they may return to their previous position. Therefore, the lines of the base topology will not be reconnected if they prevent the system performance. Afterwards a new problem is solved to find the future plan of the electrical system network with the addition of new candidate lines in the modified base topology. In order to find a more efficient plan for the future network, the proposed methodology is implemented using a Modeling Language for Mathematical Programming (AMPL) and solved using the commercial solver of CPLEX. In order to validate the proposed approach and make some comparison with the method in the literature, three test systems are conducted such as: the 24-Bus IEEE test system with 41 candidate lines, a practical case studies of 46-Bus South Brazilian system with 79 candidate lines, and the 93-Bus Colombian system with 155 candidates. For large-scale systems, in order to facilitate the implementation of the mathematical model, a strategy to reduce the search space of the buses in which the generation or demand has been presented. In the transmission expansion planning problems, usually we face with a mixed integer non-linear programming problem (MINLP) using the DC model, which make it impossible to use the linear solver of CPLEX. The strategy to overcome this problem is using the disjunctive linear model, which is a DC linear equivalent model. The ...

Neste trabalho foi apresentado uma nova modelagem matemática para problemas de Planejamento da expansão de sistemas de transmissão ao longo prazo que permite uma mudança no conceito de expansão de sistema de transmissão. Nos problemas de planejamento da expansão de sistemas de transmissão tradicionais apenas as adições de linhas candidatas são consideradas. Neste trabalho um novo conceito de planejamento da expansão do sistema de transmissão é encontrar uma nova solução para a topologia base onde todas as linhas estão temporariamente desconectadas e a implementação dessas linhas são reconsideradas quando elas podem voltar à sua posição anterior. Portanto as linhas da topologia de base não será restabelecida se impedir o desempenho do sistema. Depois um novo problema é resolvido para encontrar o plano futuro da rede do sistema elétrico, com a adição de novas linhas de candidatas na topologia base modificada. A fim de encontrar um plano mais eficiente para a rede futura, a metodologia proposta é implementada usando a linguagem de modelagem para a programação matemática (AMPL) e solucionada usando o solver comercial CPLEX. A fim de validar a abordagem proposta e fazer alguma comparação com o método na literatura, três sistemas de testes são realizados, tais como: o sistema de 24-Bus IEEE teste com 41 linhas de candidatas, um estudos de casos práticos do sistema de 46-Bus do Sul do Brasil com 79 linhas de candidatas, e do sistema colombiano 93-Bus com 155 candidatas. Para sistemas de grande porte, a fim de facilitar a implementação do modelo matemático, uma estratégia é apresentada para reduzir o espaço de busca das barras em que a geração ou a demanda. Nos problemas de planejamento da expansão da transmissão geralmente nos deparamos com um problema de programação não-linear inteira mista (PNLIM) usando o modelo DC, o que torna impossível usar o solver linear ...
Keywords: Energia eletrica - Transmissão; Topologia de redes eletricas; Modelos lineares (Estatistica); Heuristica; Electric power Transmission